Evidence of Mitochondrial Dysfunction in Bacterial Chondronecrosis With Osteomyelitis–Affected Broilers - Ferver, Alison; Greene, Elizabeth; Wideman, Robert; Dridi, Sami (Frontiers in Veterinary Science, 2021)
A leading cause of lameness in modern broilers is bacterial chondronecrosis with osteomyelitis (BCO). While it is known that the components of BCO are bacterial infection, necrosis, and inflammation, the mechanism behind BCO etiology is not yet fully understood. In numerous species, including chicken, mitochondrial dysfunction has been shown to have a role in the pathogenicity of numerous diseases. The mitochondria is a known target for intracellular bacterial infections, similar to that of common causative agents in BCO, as well as a known regulator of cellular metabolism, stress response, and certain types of cell death. This study aimed to determine the expression profile of genes involved in mitochondrial biogenesis, dynamics and function. RNA was isolated form the tibias from BCO-affected and healthy broilers and used to measure target gene expression via real-time qPCR. Mitochondrial biogenesis factors PGC-1α and PGC-1β were both significantly upregulated in BCO along with mitochondrial fission factors OMA1, MTFR1, MTFP1, and MFF1 as well as cellular respiration related genes FOXO3 and FOXO4 and av-UCP. Conversely, genes involved in mitochondrial function, ANT, COXIV and COX5A showed decreased mRNA expression in BCO affected tibia. This study is the first to provide evidence of potential mitochondrial dysfunction in BCO bone and warrants further mechanistic investigation into how this dysfunction contributes to BCO etiology.